2020
DOI: 10.1177/1029864920948575
|View full text |Cite
|
Sign up to set email alerts
|

Making the Unfamiliar Familiar: The Effect of Exposure on Ratings of Unfamiliar Musical Chords

Abstract: Affective responses to music have been shown to be influenced by the psychoacoustic features of the acoustic signal, learned associations between musical features and emotions, and familiarity with a musical system through exposure. The present article reports two experiments investigating whether short-term exposure has an effect on valence and consonance ratings of unfamiliar musical chords from the Bohlen-Pierce system, which are not based on a traditional Western musical scale. In a pre- and post-test desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 83 publications
(138 reference statements)
2
28
0
Order By: Relevance
“…The analyses were conducted in the statistical program R (R Core Team, 2014) with the brms package (using Stan) (Bürkner, 2017(Bürkner, , 2018 R Core Team, 2014). Similar approaches have been used previously in Escudero et al, (2020) and Smit et al, (2019;2020;2020a). A comprehensive overview of the methods is described in Smit et al, (2019) and Escudero et al, (2020).…”
Section: Bayesian Regressionmentioning
confidence: 99%
See 2 more Smart Citations
“…The analyses were conducted in the statistical program R (R Core Team, 2014) with the brms package (using Stan) (Bürkner, 2017(Bürkner, , 2018 R Core Team, 2014). Similar approaches have been used previously in Escudero et al, (2020) and Smit et al, (2019;2020;2020a). A comprehensive overview of the methods is described in Smit et al, (2019) and Escudero et al, (2020).…”
Section: Bayesian Regressionmentioning
confidence: 99%
“…This prior was chosen with respect to the number of independent variables and their interaction in the model compared to the number of observations per participant (24). The use of weakly informative priors and the assessment of evidence from posteriors distributions instead of single-point maximum likelihoods makes Bayesian regression models resistant to overfitting Smit et al, 2020a).…”
Section: Bayesian Regressionmentioning
confidence: 99%
See 1 more Smart Citation
“…We tested for a mere exposure effect by comparing the no exposure with the negative exposure conditions and found that the higher liking ratings for positive chords when paired with negative exposure compared with no exposure are suggestive of a mere exposure effect. In a previous study, we examined happiness and pleasantness ratings of the same chords using a paradigm that was specifically designed to test for mere exposure (Smit et al, 2020). In that study, we only found an increase in happiness ratings after exposure for negative chords, but not for the other two chord types.…”
Section: Discussionmentioning
confidence: 99%
“…Although several possible origins have been proposed 10 , there is no consensus over exactly how harmony and pitch affect our emotions and to what extent these effects are culturally mediated or universal 2,5,[14][15][16][17][18][19][20] . Experiments conducted with Western participants have shown that emotions induced by psychoacoustic features related to the pitch content of the musical signal -such as roughness, harmonicity, spectral entropy, and mean pitch -are relevant not only for familiar musical examples, but also for unfamiliar microtonal stimuli [21][22][23] . Although this suggests that harmony and melody may have the capacity to communicate universally, mixed results have been obtained from four prior experimental investigations in remote communities without access to mass media: Mafa, Cameroon 24 ; Mebenzélé Pygmies, Congo 18 ; Tsimane', Bolivia 19 ; Khow and Kalash, Pakistan 25 .…”
mentioning
confidence: 99%